Modern music, Alan Bush, and the Cold war : the cultural left in Britain and the communist bloc - Bullivant, Joanna Louise, 1983- (Music since 1900., 2017)
The first major study of British communist composer Alan Bush, providing new perspectives on music and politics during the Cold War.